1003Modifiable risk factors and incidence of diabetes mellitus progressing in the prediabetic Population. (2nd September 2021) - Hong, Kwan; Yu, Eun Sun; Chun, Byung Chul
Abstract: Background: Although the prevention of diabetes mellitus is important, factors related to its progression in the prediabetic population are rarely revealed. This study aimed to estimate the rate of progression and uncover the modifiable risk factors leading to progression. Methods: We constructed a group from the National Health Screening Cohort, consisting of adults who received national health screening tests in 2002. After selecting a prediabetic population, we classified them into two groups based on their diabetes progression after a 13-year follow up. The adjusted incidence rate was estimated, and the Cox proportional hazard modelling was performed to identify risk factors for progression. Results: The progression rate of diabetes in the prediabetic population (88, 330) was 22.85% (20, 184), with an adjusted incidence rate of 25.18 (95% confidence interval, CI: 24.44 – 26.02) per 1, 000 person-year, ages 40-64 and 25.69 (95% CI: 24.46 – 26.95) in those 65 or older. Among modifiable risk factors, smoking showed the highest hazard ratio, 1.21 (95% CI: 1.16 – 1.25), followed by BMI and alcohol consumption with hazard ratios of 1.06 (95% CI: 1.06 – 1.07) and 1.06 (95% CI: 1.02 – 1.09), respectively. Conclusions: Considering the high progression rate of the prediabetic population, modifiable risk factors, such as smoking, should be managed. Key messages: The progression rate of the prediabetic population was 25–26% per 1, 000 person-year. At the 13-year follow up, modifiable risk factors, such as smoking, BMI, and alcohol consumption, affected the prediabetic population.